Investigation of the Siderophore Production and Associated Heavy Metal Accumulation Potential of Brevibacillus laterosporus 301/İK3-2 - Özdemir, Fatma İnci; Aydın, Bahadır; Tülek, Ahmet (My University, 2023)
Siderophores are secondary metabolites released into the environment by various microorganisms, fungi, and plants to chelate iron from the surrounding environment. It is known that siderophores bind to other metals besides iron. Today, heavy metals, which are released as an undesirable result of industrial development, accumulate at high rates and pose a significant threat to biological living things. In this sense, remediation of heavy metal-contaminated sites is an urgent requirement. Siderophores are promising agents for the removal of heavy metals from natural habitats with the role of bioremediation. In this study, the effect of heavy metals on the growth and siderophore production of Brevibacillus laterosporus was investigated. Maximum siderophore production was determined as 50 % at 48 h in the metal-free growth media. In addition, maximum siderophore production was determined for various heavy metals including 5 ?M Hg2+, 0.5 mM Ni2+, 0.1 mM Co2+, and 2.5 ?M Fe2+. Intracellular uptake of the mercury was also measured using optical emission spectroscopy and compared with siderophore production values of the B. laterosporus. The maximum biosorption of mercury was measured to be 40% in 5 ?M Hg2+-containing media at 48 h of incubation. The results show that siderophore production is affected by uptake of various metals, and are usable for removing of heavy metals from environmental habitats.
Keywords: Heavy metal; secondary metabolite; Brevibacillus laterosporus; siderophore; CAS assay